Modern Principles of the Etiology and Pathogenesis of Viral Hepatitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Viral hepatitis B (HBV) is one of the most significant modern health problems, affecting millions of people worldwide. This infectious disease caused by the hepatitis B virus can lead to serious health consequences, including chronic infection, liver cirrhosis, and primary liver cancer (hepatocellular carcinoma). Despite significant progress in the development of diagnostic and treatment methods, HBV remains a global problem that requires close attention and effective control measures.